Vitamin D and orthodontics: an insight review - Almoammar K (Dove Medical Press, 2018)
Khalid Almoammar Department of Pediatric Dentistry & Orthodontics, College of Dentistry, King Saud University, Riyadh, Saudi Arabia Abstract: Vitamin D is known as the oldest of all hormones. 7-Dehydrocholesterol is converted to previtamin D3. It becomes a secosteroid when it is later converted to 1,25-dihydroxyvitamin D3 (1,25(OH)2D3). A number of factors influence vitamin D3 production, including skin pigmentation, the use of sunscreen lotions, season, latitude, and altitude. Vitamin D is important for bone metabolism and calcium hemostasis. Researchers have linked a deficiency in vitamin D levels to a number of systemic complications, including cardiovascular disease, diabetes, immune deficiency, and infectious diseases. In orthodontics, laboratory studies have revealed some evidence that vitamin D enhances tooth movement and the stability of the tooth position. This review is an attempt to understand the role and systemic consequences of vitamin D deficiency and to examine its relevance to orthodontics. Keywords: orthodontics, tooth movements, vitamin D, vitamin deficiency